IDENTIFIKASI KOMODITAS UNGGULAN UNTUK PENINGKATAN DAYA SAING BIOFARMAKA DI SUMATERA UTARA - Rita Herawaty Bangun (JURNAL AGRICA, 2019)
This study aims to identify superior biopharma commodities that are priority commodities to be developed and priority areas for the development of biopharma leading commodities in Sumatera Utara Province. The analytical methods used were descriptive analysis, location quotient analysis, and shift-share analysis. The results showed that the leading biopharma commodities in Sumatera Utara Province were ginger, turmeric, and dlingo and the regions that had the potential to develop ginger and turmeric were Simalungun and Toba Samosir Regencies while the potential for dlingo development was Langkat Regency.